PENDIDIKAN KARAKTER BERBASIS PEMBIASAAN DALAM MEMBENTUK DISIPLIN ANAK USIA DINI - Asnah; Marhamah (STAI Nusantara Banda Aceh, 2025)
Character education is an essential aspect of early childhood development, particularly in fostering discipline as a foundation for positive behavior in later stages of life. One of the most effective approaches to cultivating disciplinary character is through habituation practices that are consistently implemented in both family and educational environments. This study aims to analyze the role of habituation-based character education in developing discipline among early childhood learners and to identify forms of habituation that support character development. The study employed a library research method by reviewing relevant books, scientific articles, and previous studies related to character education, habituation, and discipline in early childhood. The findings indicate that consistent and repetitive habituation practices, such as arriving on time, maintaining cleanliness, obeying rules, and taking responsibility for simple tasks, effectively foster children's disciplinary attitudes. The success of character formation is influenced by the role modeling of parents and teachers, the consistent implementation of rules, and strong collaboration between families and schools. Therefore, habituation-based character education is an effective approach to developing discipline in early childhood by enabling children to internalize positive values through continuous daily experiences.